KONSEP HAK MILIK DALAM ISLAM - Ahmad Sainul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
The definition of property rights is the same, namely that property or ownership is a relationship of ownership between humans and assets or objects applied by syara ', which provides powers that allow us to take advantage of or carry out tasarruf over these assets or objects in ways that are justifiably stipulated. By syara '. The system of ownership has been described much by jurisdictorials as that property rights are divided both it is perfect and impective.In addition to ownership types of individual, public ownership, and state ownership with various conditions in it. Present The causes and ways of Obtaining ownership between other because of work, inheritance, Giving state assets to the people, Assets acquired without compensation for assets or personnel, and individual gain.Wisdom and Property Rights between other: Humans may not own property carelessly, without knowing the applicable rules that have been revealed by Islam. Humans will have the principle that looking for wealth must be in ways that are good, correct and lawful. Owning property is not an absolute right for humans, but is a mandate (entrusted) from Allah SWT. What must be used and utilized as much as possible for the benefit of human life and channeled in the way of Allah to obtain His approval. Last of islam banks Taking Other People Ownership in Wrong Ways